POTRET TAMADDUN ISLAM DI NEGERI “TIRAI BAMBU” (Mulai dari Masa Dinasti Tang hingga Republik Rakyat China) - Asmanidar Asmanidar (Universitas Islam Negeri Ar-Raniry, 2015)
China is a very unique country, has a very old civilization and culture in the world. Under the glory and the strength “Great Wall”, China emperium kept a million secreet about Islamic history and civilization which started from Tang Dinasty, Sung Dinasty, Yuan Dinasty, Ming Dinasty up to Manchu Dinasty (Ching Dinasty). Actually, Islam in China, In the erliest days, brought through two ways by Arabian and Parsian traders, namely silk road and sea road. Even both of those ways had it’s own difficulties. One of the famous moslem who spreading and introducing Islam in that area that was Sa’ad bin Abi Waqas through “Silk Road” at least on 4th or 5th centuries based on several trusted resources. Sa’ad had a special respect from Yung Wei as a China emperor from Tang Dinasty at that time. Since then, gradually Islam stepped in foot in this area even dinasty to dinasty has been changed till China became Republic, and the Communist regime reigned China. However, the spirit of moslem minority in China was never faded out upto now. The Islamic preaching which was brought by brilliant and pious traders (Arabs and Parsians) in 1.400 years ago, truely left the greatest influences, not only perceptions but also values of moslem society in China nowdays. Whether realize or not, the Chinese people have already adopted many knowledges from Islamic people from time to time.